The Effect of Changes to Nickel Coating Machine on Surface Integrity and Microstructure after Grinding - Marek, Martin; Novák, Martin; Holešovský, František; Durakbasa, Numan M.; Walcher, Eva Maria (Manufacturing Technology Journal, 2017)
Grinding is an overly used finishing technology, which can obtain very accurate surface integrity. The desirable surface quality after grinding is one of the most relevant parameters. In production, surface preparation such as chromium plating, nickel plating, etc. are more prevalent. These platings are used as protection against corrosion, erosion, abrasion and as a material for the renovation of worn parts. This paper discusses the change of nickel coating machines, which has an influence on surface integrity and microstructure after grinding. The team has built a completely unique and new technical solution for the covered equipment which had never been built in the past. The input parameters were selected based on past experience in the company, related to the area covered in this paper.
Keywords: nickel; grinding; surface integrity; microstructure